The Role of Social Protection Fiscal Policy in Supporting Indonesia’s Economic Recovery During the Covid-19 Pandemic: Evidence from a CGE Model - handayani, Rita; C. Sugianto; J. Saputra (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2025)
The Computable General Equilibrium model is used to build a general equilibrium model of the Indonesian economy, to see the effectiveness of the impact of fiscal policy on social protection during the Covid-19 Pandemic on economic growth and household group income for the 2019-2021 period. The PEP -1-1 model is used with the static version 2.0 in GAMS 23.5 software with social protection variables simulated as a shock to the model that has been built. The results explain that there is an impact and contribution of social protection to Indonesia's macroeconomic conditions and economic recovery and sustainable growth during the Covid-19 Pandemic and out of the crisis. The results of social protection fiscal policy carried out by the government were able to contribute to an increase in economic growth by 0.03 per cent. The results of fiscal policy on social protection provided by the Government also had an impact on increasing the highest level of income in the hhk6 household group, namely upper-class free entrepreneurs, non-agricultural entrepreneurs, managers, military, professionals, technicians, teachers, TU workers and upper-class sales, Urban) by 06 percent, while other household groups were only able to increase by 0.1 percent.